Ultrasound-assisted Extraction and Characterizations of Pectins from Dragon Fruit (Hylocereus polyrhizus) Peels in Various Acid Solution: A Preliminary Study - Rubaiyi, M. Zaid; Zularisam, A. W.; Mimi Sakinah, A. M. (2016)
The worldwide consumption of pectin was reported about 45 million kilogram per annum. Due to some major demand of pectin in food and pharmaceutical industries, numerous investigations have been carried out to determine the composition of pectin in different plant. A major challenge in developing any new pectin product is to preserve the physicochemical characteristics of pectin. This is due to composition of pectin can vary depending on the plant source and extraction condition. This study was focused on the potential of Hylocereus polyrhizus peels (HPP) to be a source of pectin. The extraction of pectin from HPP was carried out using combine method of physical and chemical during extraction. The equipment used was sonicator bath attach with propeller stirrer and extraction was carried out in dionized water, organic acid (citric acid, acetic acid) and mineral acid (H2SO4, HCl, HNO3). Pectin obtain from this method was compared in terms of yield, galacturonic acid (GalA) content and degree of esterification (DE). Fourier Transform Infrared Spectroscopy (FTIR) and Ultra Violet-visible spectroscopy (UV-vis) was used in the identification of HPP pectin properties. The yield of HPP pectin range obtained was from 33% to 40% with the GalA content from 22% to 40% and DE from 13% to 62%. The highest pectin yield (~40%) with GalA 39% and DE 62% can be achieved when extraction was carried out using citric acid solution. These results suggest that ultrasound-assisted extraction could be a good option for the pectin extraction with citric acid from HPP for industrial scale.